2020
DOI: 10.1007/s00167-020-05966-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep gluteal syndrome is defined as a non-discogenic sciatic nerve disorder with entrapment in the deep gluteal space: a systematic review

Abstract: Purpose Clinicians are not confident in diagnosing deep gluteal syndrome (DGS) because of the ambiguity of the DGS disease definition and DGS diagnostic pathway. The purpose of this systematic review was to identify the DGS disease definition, and also to define a general DGS diagnostic pathway. Methods A systematic search was performed using four electronic databases: PubMed, MEDLINE, EMBASE, and Google Scholar. In eligibility criteria, studies in which cases were explicitly diagnosed with DGS were included, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
(79 reference statements)
0
22
0
3
Order By: Relevance
“…A total of 3 artistic athletes (2 competitive dancers and 1 recreational dancer) could not return to artistic activities due to postoperative deep gluteal syndrome (DGS) as a complication. 9 , 23 These 3 patients underwent continued physical therapy and occasional ultrasound-guided injection of 1 mL of 1% bupivacaine and 9 mL of normal saline. One of them underwent surgical decompression of the sciatic nerve and posterior femoral cutaneous nerve in a deep gluteal space.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 3 artistic athletes (2 competitive dancers and 1 recreational dancer) could not return to artistic activities due to postoperative deep gluteal syndrome (DGS) as a complication. 9 , 23 These 3 patients underwent continued physical therapy and occasional ultrasound-guided injection of 1 mL of 1% bupivacaine and 9 mL of normal saline. One of them underwent surgical decompression of the sciatic nerve and posterior femoral cutaneous nerve in a deep gluteal space.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, 3 dancers (13%) experienced postoperative DGS, defined as a nondiscogenic sciatic nerve with entrapment in the deep gluteal space. 9 The diagnosis of DGS was based on a detailed clinical history, including a description of the current condition, date of onset, mechanism of injury (traumatic or nontraumatic), factors that increased or decreased pain, prior consultations, prior surgical interventions, pain level, and narcotics use. A recent study 23 in a series of 1167 patients undergoing hip arthroscopy reported that the incidence of postoperative DGS was 0.9%, and predictors for postoperative DGS after hip arthroscopic surgery were female sex, generalized joint laxity, multiple hip surgical procedures, and acetabular dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, pain at this level is classed as “deep gluteal pain” (Fernández‐Hernando et al, 2015, 2016; Kizaki et al, 2020; Martin et al, 2011; Pérez‐Carro et al, 2016). This indicates the etiopathogenic complexity of the process and therefore its symptoms and exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Except for hamstring tears, I have found the IFI and particularly the SNE diagnosis to be challenging, and I agree with Park et al that many physicians remain unfamiliar with the concept of deep gluteal syndrome. 11 Clinical assessment of deep gluteal syndrome, defined as nondiscogenic sciatic nerve entrapment, 12 can be difficult but is critical and one of the skills that we as hip sports surgeons, need to master. 4 As Aguilera-Bohórquez et al mentioned, their study was not without limitations; nonetheless, this is a valuable study, and I applaud the work presented.…”
Section: Reported No Neurologic Ormentioning
confidence: 99%